Investigation of mechanisms of mitotic recombination in yeast - Harcy, Lisa Victoria, author; Argueso, Lucas, advisor; Di Pietro, Santiago, committee member; Liber, Howard, committee member; Suchman, Erica, committee member (Colorado State University. Libraries, 2016)
At the submicroscopic level within all living cells the workings of a dynamic molecular world attempt to preserve the integrity of DNA - the blueprint of life. This dissertation describes in detail the experimental systems and results from two of our studies conducted in which DNA lesions compromised genomic integrity. The unifying theme of the following chapters revolves around the mechanisms responsible for structural genomic variation, that is, what happens to chromosomes when they break. In the first phase of research, we examined outcomes associated with double-strand breaks (DSBs) at G-quadruplex DNA sequences. Here, we show that G4 DNA motifs, capable of initiating double-strand breaks, result in the formation of chromosomal aberrations. Our results provide structural context and support to a putative mechanism of homology-directed repair revealed by molecular analysis of these complex rearrangements. In the second project, we investigated chromosomal translocations that developed from spontaneously occurring DSBs in diploid yeast to ascertain the means by which the DSBs had been repaired. The objective of this study was to examine the intricate interplay between the non-allelic DSB repair (DSBR) processes: canonical reciprocal homologous recombination (CRHR) vs. break-induced replication (BIR). While numerous assays have previously measured repair pathway efficiency by isolating one of the two pathways from the other, no prior studies to our knowledge, have prospectively examined the contribution of BIR to overall double-strand break repair in diploids, using a non-inducible experimental system where either mechanism can be used freely by the cells. I designed and constructed a new assay system to study chromosomal translocations in the yeast eukaryotic model to investigate the balance between these two DSB repair processes. I characterized genotypic and phenotypic alterations in wild type background and in mutant yeast strains defective for BIR. The data obtained from this work provides an additional perspective to the field of DNA repair biology with broad relevance to DSBR regulation in eukaryotes. It provides further understanding about the role of DNA repair to undesired genetic outcomes, thus, leading the way to the design of new and more effective treatments for diseases in which these molecular actions are the instigators of pathogenesis.
Keywords: chromosomal rearrangement; genome stability; non-reciprocal translocation; break-induced replication; g-quadruplex; DNA repair